From shadow to person: Exploring roles in participant observations in an eldercare context. (May 2014) - Börjesson, Ulrika
This article explores participant observation as a research method and more specifically addresses the intriguing situation of the researcher's role in interacting with participants in the setting. The materials used in the analysis are field notes from participant observations focused on staff at two eldercare units in a mid-sized city in Sweden. Because limitations when referring to Raymond Gold's roles of participant observations are known but sparsely described and discussed, this text attempts to provide that description and discussion. The specific question posed in the article is, (How) do roles for the researcher in participant observations change during the course of fieldwork? Randall Collins' theory on interaction ritual chains is used as an analytical tool to identify symbols in the two staff groups. The examples chosen from the field are symbols displayed at the units, which moreover illustrate that the researcher's roles in participant observations not only change once or twice during the course of fieldwork but also change continuously. Consequently, fieldworkers shift roles in different situations when observing a variety of people and settings. Observations are developed in the interaction between the researcher and the participants; therefore, referring observations to a number of roles is restrictive and limiting.